The impact of the herbicide and biologic preparations on the weediness and crop density of chickpea - Карпенко, В. П.; Коробко, О. О. (Scientific Progress & Innovations, 2018)
The article provides the results of the investigation of the impact of the herbicide «Panda», the plant growth regulator «Stympo» and the microbial preparation «Ryzobofit» on the weediness and crop density of chickpea of the breed Pamiat in the conditions of Right-Bank Forest-Steppe of Ukraine. We established the connection between the act of different limits of the herbicide «Panda», the plant growth regulator «Stympo» (0.025 l/t) and the microbial preparation «Ryzobofit» (1.0 l/t), the quantitative content of weeds and the density of crop plants of chickpea. We determined the effective action of the herbicide against growing in grain fields in limits 3.0–4.0 l/ga. It was investigated that the least amount and mass of weeds in crops, without substantial decrease of cheakpea density, was distinguished while combining the soil herbicide «Panda» in limits 3.0–4.0 l/ga, the plant growth regulator «Stympo» (0.025 l/t) and the microbial preparation «Ryzobofit» (1.0 l/t). The joint effect of the herbicide and the biological preparations in the given variants of the investigation provided the decrease of weediness of crops in the amount against the control I on 76–85%. Moreover, the density of plants decreased only on 2–3%. On the base of the conducted experiments the most efficient combination of the usage of preparations was determined – the growth regulator «Stympo» (0.025 l/t), the microbial preparation «Ryzobofit» (1.0 l/t) and the soil herbicide «Panda» in limits 3.0–4.0 l/ga, which provides the increase of crop productivity, decrease of their weediness and which is environmentally friendly.